Experimental research on safety impacts of the inside shoulder based on driving simulation - Zhao, Xiaohua; Ding, Han; Wu, Yiping; Ma, Jianming; Zhong, Liande (Accident analysis and prevention, 2015)
•We tested the safety impacts of inside shoulder.•We did an empirical research based on a driving simulator.•We used the repeated measures analysis of variance (rANOVA) and the contrast analysis.•Inside shoulder would influence subjects’ heart rate and eye movement, and have statistically significant effects on vehicle’s lateral position.•The desired inside shoulder width should be between 0.75m and 1.5m, with 1.5m being the optimal inside shoulder width for eight-lane, two-way divided expressways. Statistical data shows that single-vehicle crashes account for half of all traffic crashes on expressways in China, and previous research has indicated that main contributing factors were related to whether and how the inside shoulder was paved. The inside shoulder provides space for drivers to make evasive maneuvers and accommodate driver errors. However, lower-cost construction solutions in China have resulted in the design of numerous urban expressway segments that lack inside shoulders. This paper has two objectives. The first is to reveal the safety impacts of inside shoulders on urban expressways by driving simulator experiment. The second objective is to propose optimal range and recommended value of inside shoulder width for designing inside shoulders of urban expressways. The empirical data, including subjects’ eye movement data, heart rate (HR) and the lateral position of vehicles, were collected in a driving simulator. The data were analyzed to evaluate the safety impacts of the inside shoulder. The results have revealed that the inside shoulder has an impact on drivers’ visual perception, behaviors, and psychology; in particular, it has a significant effect on vehicle operations. In addition, this paper recommends the desired and optimal inside shoulder widths for eight-lane, two-way divided expressways.